Souhaits oubliés : documents de fin de vie des personnes trans vivant avec une démence aux marges des changements juridiques - Alexandre Baril; Marjorie Silverman; Marie-Claire Gauthier; Maude Lévesque (Glad!)
Literature on the topic of trans older adults has documented a few anecdotal cases in which some trans people living with dementia forgot they transitioned and reidentified with their sex assigned at birth (“detransition”). Trans communities and their allies have encouraged trans people to engage in end-of-life planning, including the preparation of legal documents that state their wishes regarding gender identity and expression in the event of “incapacity” caused by dementia. While useful, we contend that end-of-life planning is often implicitly based on cisnormative and cogninormative (normative system based on cognitive abilities) assumptions. Such planning is founded on a stable notion of gender identity throughout the life course (“post-transition”) and assumes that the pre-dementia self is better equipped to make decisions than the “demented” self. We conclude by encouraging, based on an intersectional, trans-affirmative, crip-positive, and age-positive approach, respect for the agency of trans people with dementia.